VIOLATION OF UN SECURITY COUNCIL RESOLUTION 1244 (Proceedings of the International Scientific Conference "Social Changes in the Global World", 2023)
The issue of Kosovo's disrespect for resolution 1244 has significant implications for the United Nations and the international legal system. The failure to respect and implement resolution 1244 has undermined the authority of the UNSC and the international community's commitment to upholding international law. The policy debate on Kosovo's independence has been divided, with some countries such as the European Union and the United States supporting Kosovo's independence as necessary for the stability and development of the region, while other countries like Russia and China oppose it as a violation of international law. This has led to a lack of consensus on the implementation of resolution 1244, which is crucial for ensuring peace and stability in the region. The relevant literature highlights the need for a balanced approach that takes into account the complexities of the issue and promotes a peaceful solution through dialogue and negotiations. It also emphasizes the importance of supporting the development of Kosovo as an independent state while respecting the principle of territorial integrity. The UN's capacities for the prevention of violent conflict have also been discussed as an important tool for addressing the issue of Kosovo's disrespect for resolution 1244.The issue of Kosovo's disrespect for resolution 1244 is a complex and contentious issue that requires careful consideration and analysis. Keywords relevant to this issue include self-determination, territorial integrity, international law, United Nations, UNSC, policy debate, and development. A balanced approach that promotes peace and stability in the region while respecting international law and the United Nations system is essential for a sustainable solution.
Keywords: 1244, Kosovo, Serbia, conflict